A New Stability- Indicating RP-HPLC Method to Determine Etamsylate in Injection Formulation. - S, Chandrshekhara (International Journal of Pharmaceutical & Biological Archive, 2010)
A simple and accurate Reverse Phase High-Performance Liquid Chromatography (RPHPLC) method was developed to determine Etamsylate in injection formulations. The drug was chromatographed on a reversed phase C-18 column. Eluents were monitored at a wavelength of 220 nm using a mixture (40:60) Methanol: Buffer (phosphate buffer). Solution concentrations were measured on weight basis to avoid the use of an internal standard. The method was spastically validated for linearity, accuracy, precision and selectivity. Due to its simplicity and accuracy, method will be useful for routine quality control analysis. <!--[if !supportEmptyParas]--> <!--[endif]-->